ANALISIS PENGARUH WORK-LIFE BALANCE TERHADAP ETOS KERJA KARYAWAN GENERASI Z DI PERUSAHAAN TEKNOLOGI DI ERA MODERN - Daryoto Mulyadi Candra (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The rapid advancement of technology has influenced work patterns and the preferences of the new workforce generation, particularly Generation Z. One of the key issues in human resource management today is how to maintain employee work ethic without neglecting the need for work-life balance. This study aims to analyze the effect of work-life balance on the work ethic of Generation Z employees in technology companies. The research method used is a quantitative approach with a survey technique involving 100 respondents who are Generation Z employees in three technology companies in Jakarta. Regression analysis results show that work-life balance has a positive and significant effect on work ethic. These findings indicate that companies need to design flexible and adaptive work policies that accommodate the personal needs of young employees to enhance their enthusiasm, dedication, and sense of responsibility at work.